Use of Arduino in the Development of a New and Fast Automated Online Preconcentration System Based on Double-Knotted Reactor for the Mn Determination in Tea Samples by Flame Atomic Absorption Spectrometry (F AAS) - Barreto,Jeferson A. (2020)
In the present paper, an automated online preconcentration system based on the use of two knotted reactors (KR) was developed for Mn determination in tea samples by flame atomic absorption spectrometry (F AAS). The system automation was performed by using four solenoid valves to switch sample streams and reagents. Valves were driven electronically by an integrated Darlington transistor circuit and controlled by an open-source Arduino hardware platform written in C language. The preconcentration was based on the precipitation process of metal ions complexed with 2-(5-bromo-2-pyridylazo)-5-(diethylamino)phenol (5-Br-PADAP) on the inner walls of the reactor, followed by elution with a solution of hydrochloric acid. The optimized system allowed the Mn determination with limit of detection (LOD) of 2.1 mg L-1, precision (relative standard deviation (RSD), 50.0 mg L-1) of 2.6% and enrichment factors of 8. The system presented a sampling frequency of 60 h-1. The method accuracy was evaluated by analysis of the certified reference material (CRM) apple leaves (NIST 1515) and by addition/recovery tests obtaining recoveries between 95.2 to 119%. This method was applied in the Mn determination in commercial tea samples purchased from local trade. Manganese levels were found in a concentration range of 2.95 to 123 µg g-1.